Nutritional Status, Family Support and Dietary Habit among Tuberculosis Patients: An Overview (Indian Journal of Public Health Research & Development, 2020)
Objectives: This research aimed at identifying Nutritional Status, Family Support and Dietary Habit amongTuberculosis PatientsMethod: A cross-sectional study was set up as a method. In selecting the subjects, purposive sampling wasused by referring to the set inclusive criterion, which was that the patients were in the intensive phase. Toend up, as many as 38 patients diagnosed with tuberculosis were recruited as the respondents. Chi-squaretest was used for data analysis of this current research.Results: The majority of the respondents were reportedly equipped with abnormal nutritional status bysignifying 52.6%. Meanwhile, the rest 18 participants, signifying 47.4%, had shown normal nutritionalstatus. More than half of the whole respondents (52.6%) had normal nutritional status, while the rest(47.4%) of whom showed abnormal condition. Both of the groups of respondents, with regular and abnormalnutritional statuses, received poor familial support, with 61.1% (11 respondents) in the former and 60% (12respondents) in the latter.Conclusion: More than half of the whole respondents had normal nutritional status. More than half of therespondents with good dietary habit had normal nutritional status. Both of the groups of respondents, withregular and abnormal nutritional statuses, received poor familial support
Keywords: Nutritional status, tuberculosis, Community Health Center.